(untitled) (Journal of Governance and Development (JGD), 2023)
Corruption is the great ailment that disturbed most of the nation states across the globe, its predicament is worst in the developing states than developed one. The sinister of corrupt practices have attracted the attention of international community to designed some strategies for combating its menace, this has adversely makes the member states to masterminds their strategies or review the existent one for enhancing probity, accountability and national development. This study compares the strategies for combating corruption between Nigeria and Iraq. The study employed qualitative techniques through interview method in obtaining data from the stakeholders, academics and politicians. The study revealed that both Nigeria and Iraq have institutional strategies for fighting against grafts in their country. It was also revealed that the strategies are effective in Nigeria while they are ineffective in Iraq; it also pointed that all strategies were facing some challenges such as autonomy, political interference, and funding, inadequate staff among others. The paper recommends that the anti-grafts institutions should be strengthen, holistic approach, and enhancing political will towards discarding the above challenges facing the institutions. The role of the media and civil society should also be recognized in fighting against corruption in their respective states.